Relationship between psychological capital and engagement: Case of a basic educational institution in northeastern Peru - Agurto Cortez, Médaly Belén (2025)
Psychological capital directly influences well-being and job performance. On the other hand, engagement refers to the level of commitment, energy, and dedication an individual invests in their work. This study aimed to analyze the relationship between psychological capital and engagement among the staff of Colegio Particular Simón Bolívar, located in San Martín, Peru. A basic, quantitative, non-experimental, and correlational research design was employed, using a survey to measure both variables in a sample of 125 employees. The results of the Spearman’s Rho coefficient revealed a strong and positive relationship between psychological capital and engagement (Rho = 0.720; p = 0.000). It is concluded that any effort aimed at enhancing and promoting psychological capital will contribute to increasing engagement among workers.